The textual criticism of Sumerian literature - Delnero, Paul (Journal of cuneiform studies / / Supplemental series, 2012)
Introduction -- Mechanical errors -- Local and regional variation -- Diachronic variation -- Variants in sources compiled by the same scribe or group of scribes -- Idiosyncratic variants -- Interpretive variants -- Procedure for evaluating textual variation -- Conclusion